PENGEMBANGAN MEDIA KARTUN UNTUK PEMBELAJARAN MENULIS TEKS DIALOG SESUAI DENGAN UNGGAH-UNGGUH BASA PADA SISWA SMP DI KABUPATEN BATANG - yulianna, pegi (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2019)
The purpose of this research is due to lack of student learning motivation and lack of learning media, so it needs the development of cartoon media as a medium for learning to write dialog texts. This study uses a Research and Development (R&D) approach. Research steps are potential and problems, data collection, product design, design validation, design revision, and limited trials. Data collection used observation techniques, interviews, questioners, and expert assessment sheets. Data analysis used qualitative and quantitative descriptive analysis techniques. Cartoon media product design contains themes and cartoon image. The result of the questionnaire needs analysis showed that teachers and students need learning media. The result of the validation of media and material experts, cartoon media increased after using the media. Based on the results of this study, it can be concluded that the cartoon media is effectively used for learning on dialog texts writing. Keywords: learning media, cartoon media, writing dialogue.